Role of transient silicon limitation in the development of cyanobacteria blooms in the Guadiana estuary, south-western Iberia - Rocha, C. (2012)
The Guadiana estuary, located between Portugal and Spain, has the fourth largest drainage basin of Iberian river systems. Up to 75% of the catchment area has been regulated by dams since the early 1970s. During the 1980s and 1990s, an increasing occurrence of summer cyanobacteria blooms dominated by the potentially toxic Microcystis spp. was reported. In an effort to understand the causes of recurrent noxious blooms in the Guadiana estuary, nutrients (phosphorus, nitrogen [nitrate, nitrite and ammonium], and silicon [silicic acid], chlorophyll a and phytoplankton abundance, specific composition and biomass were evaluated during field surveys, from April 1997 to March 1998. A pattern of successive blooms of different phytoplankton assemblages was observed throughout this period. Diatoms (nano-sized, chain-forming) dominated an early spring bloom (max. 18 × 103 cells ml–1) in March and April. Following the decrease in diatom abundance, a chlorophyte bloom (max. 11 × 103 cells ml–1) and then a cyanobacteria bloom (>6 × 104 cells ml–1) quickly followed during late spring through to early summer. From July to September, a major cyanobacteria bloom dominated by the potentially toxic Microcystis spp. (> 4 × 105 cells ml–1) developed in the freshwater zone. The results indicate that high winter loads of nitrogen and phosphorus led to the depletion of silicate (down to as low as 0.2 μM) during the early spring diatom bloom, which conditioned the successive phytoplankton assemblages during the remaining productive period. Low monthly discharge rates during spring and summer further provided an environment with low Si:N and N:P relative availability which, coupled with high water-column temperature (>21°C), seemed to favour the dominance of cyanobacteria over chlorophytes during the summer.